The Principle “Private Harm May Be Tolerated To Prevent Public Harm” And Its Role In Supporting Neonatal Food Security: An Analytical Jurisprudential Study - Abdullah Al-Qathami, Eman Mohammed (Journal of Neonatal Surgery, 2025)
This study offers a foundational and objective-based analysis of the Islamic legal maxim “private harm may be tolerated to prevent public harm”, considering it a central jurisprudential rule applicable in cases of conflict between interests or harms, particularly in emergencies and exceptional circumstances. The research explores the relationship between this principle and food security systems, focusing on newborns as the most medically and legally vulnerable group. The study adopts an analytical approach, without delving into applied details, aiming instead to connect the principle with concepts of harm in Islamic thought, the higher objectives of Sharia (maqasid), and modern medical ethics. Findings highlight the importance of defining concepts like harm, public interest, and proportionality before applying the principle. The study further emphasizes the need to integrate it into flexible legal frameworks for critical cases, balancing the protection of life with the safeguarding of individual rights